Selenium-enriched Bacillus subtilis yb-114246 improved growth and immunity of broiler chickens through modified ileal bacterial composition - Jiajun Yang (Nature Portfolio, 2021)
Abstract Here, a Selenium-enriched Bacillus subtilis (SEBS) strain was generated and supplemented to broiler chickens’ diet, and the impact in ileum bacterial microbiome, immunity and body weight were assessed. In a nutshell, five hundred 1-old old chicken were randomly divided into five groups: control, inorganic Se, Bacillus subtilis (B. subtilis), SEBS, and antibiotic, and colonization with B. subtilis and SEBS in the gastrointestinal tract (GIT) were measured by fluorescence in situ hybridization (FISH) assay and quantitative real-time polymerase chain reaction (qPCR). In summary, Chicks fed SEBS or B. subtilis had higher body weight than the control chicks or those given inorganic Se. SEBS colonized in distal segments of the ileum improved bacterial diversity, reduced the endogenous pathogen burden and increased the number of Lactobacillus sp. in the ileal mucous membrane. Species of unclassified Lachnospiraceae, uncultured Anaerosporobacter, Peptococcus, Lactobacillus salivarius, and Ruminococcaceae_UCG-014, and unclassified Butyricicoccus in the ileal mucous membrane played a key role in promoting immunity. Inorganic Se supplementation also improved bacterial composition of ileal mucous membranes, but to a less extent. In conclusion, SEBS improved performance and immunity of broiler chickens through colonization and modulation of the ileal mucous membrane microbiome.